Efektivitas Penggunaan Buku Pop-Up Pada Pembelajaran Tematik Ditinjau dari Hasil Belajar Kelas III Madrasah Ibtidaiyah Asy-Syafi’iyah - Salsabila, Annisa; Raehang, Raehang; Agus, Imaludin (Diniyah: Jurnal Pendidikan Dasar, 2023)
This study aims to find out the effectiveness of using Pop-Up book media in thematic learning of grade III of Madrasah Ibtidaiyah Asy-Syafi'iyah. The type of research used in this study is quantitative research with pre-experiment method. The research design used is One Group Pretest-Posttest Design. The population in this study is all students in grade III of Madrasah Ibtidaiyah Asy-Syafi'iyah consisting of classes III A and III B, the population is too much so the researcher chooses the population by using the sample technique "probabily sampling" with cluster sampling type, by drawing or shuffling lottery where class III A and III B are used as a lottery, so the researcher gets class III A as the research subject. Learning outcomes data obtained from pretest and posttest results in the form of multiple choice. The results obtained are the average pretest score obtained is 77.27 while the average posttest obtained is 93.18 with an average N-Gain value of 0.69 with a moderate category, this shows that the use of Pop-Up book media has succeeded in improving the learning outcomes of third grade students of Madrasah Ibtidaiyah Asy-Syafi'iyah. This is evidenced by the results of hypothesis testing which shows that the Sig value. (2-Tailed.) is 0.000